Реліктові форми жертвоприношень у весняному календарно-обрядовому фольклорі Західного Полісся - Бойчук, Олена; Boychuk, Olena (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто різні форми пожертви, збережені у весняному кален- дарно-обрядовому фольклорі Західного Полісся. Знайдено відомості про люд- ські жертвоприношення та офірування у вигляді продуктів харчування. З’ясова- но трансформацію суті та змісту жертовних обрядів у визначений календарний період.The author of the article analyses a spring calendar-ceremonial folklore of the Western Polissya, where notices the old forms of sacrifices. Concentrated attention on such actions: “send-off or exile of Winter”, baking of ceremonial thin captain, holiday of the Yurij. The analysis of these moments shows that the form of victim changes during all spring period. At the beginning of spring – it doll-scare-crow, which reflects informations about the human sacrifices. Purpose of such victim – to get the desired spring moisture (rain). The method of destruction of doll retains also information about the different forms of ceremony of interment. In more late ceremonies of spring period the role of victim is carried out by food stuffs: ceremonial thin captain, mush, bread, pies, eggs. Such victim, especially in the field, keeps an expressive agrarian value – increase of the crop. Similar transformations of victim betide in a summer calendar-ceremonial folklore.
The Relict Forms of Sacrifices in a Spring Calendar- Ceremonial Folklore of the Western Polissya
Keywords: офіра (жертва); весняний календарно-обрядовий фольклор; Західне Полісся; поле; вода; солом’яна лялька; Купало; ophir (the sacrifice); calendar-ceremonial folklore; the Western Polissya; the field; the water; the straw doll; Kupala